Use of scalp cooling device to prevent alopecia for early breast cancer patients receiving chemotherapy: A prospective study. Issue 7 (14th December 2019) - Giarratano, Tommaso; Frezzini, Simona; Zanocco, Monica; Giorgi, Carlo Alberto; Mioranza, Eleonora; Miglietta, Federica; Griguolo, Gaia; Falci, Cristina; Faggioni, Giovanni; Tasca, Giulia; Di Liso, Elisabetta; Vernaci, Grazia; et al.
Abstract: Chemotherapy‐induced alopecia (CIA) affects the majority of patients receiving chemotherapy (CT) for early breast cancer. It is a highly distressing side effect of CT, with psychological and social impact. Primary aim of the present analysis was to assess the efficacy of scalp cooling with DigniCap® in preventing CIA. Success rate was defined as patients' self‐reported hair loss <50% according to Dean scale. In this analysis, we reported success rate at 3 weeks after the first CT course and at 3 weeks after the last CT course. Secondary endpoints included self‐reported tolerability and patients' judgment on scalp cooling performance. Consecutive early breast cancer patients admitted to Istituto Oncologico Veneto who were recommended to receive neoadjuvant or adjuvant CT, were eligible to undergo scalp cooling during the CT administration within this study. 135 patients were included: 74% received adjuvant CT and 26% neoadjuvant CT ( P < .001). The type of CT was: docetaxel‐cyclophosphamide (26%), paclitaxel (23%), epirubicin‐cyclophosphamide followed by paclitaxel (32%), and paclitaxel followed by epirubicincyclophosphamide (19%). The rate of success in preventing alopecia was 77% (104/135) at 3 weeks from the start of CT and 60% (81/135) at 3 weeks from the end of treatment. Higher success rates were reported in non‐anthracycline (71%) compared to anthracycline‐containing CT regimens (54%; P < 0.001). Premature discontinuation of scalp cooling was reported in 29/135 patients (21.5%), including withdrawal for alopecia (16/29), for low scalp cooling tolerability (8/29) or both (5/29). Scalp cooling was generally well tolerated. These results overall suggest that the use of scalp cooling is effective in preventing alopecia in the majority of early breast cancer patients receiving neoadjuvant or adjuvant CT, especially for patients undergoing a taxane‐based non‐anthracycline regimen.